Diagnostics for Citrus exocortis and Hop stunt viroids associated with yellow corky vein disease in citrus - J. AGARWAL and Y.S. AHLAWAT, P. RAMACHANDRAN*, A. ROY, S. MATHUR (Indian Phytopathology, 2003)
The techniques of return polyacrylamide gel electrophoresis (R-PAGE), reverse transcriptase polymerase chain reaction (RT-PCR) and nucleic acid spot hybridization (NASH) were evaluated with special reference to yellow corky vein disease infecting Kagzi lime plants. The technology for quick and reliable detection of two different groups of viroids viz. Citrus exocortis viroid (CEVd) and Hop stunt viroid (HSVd) infecting citrus has been standardized for the first time in the country. The tools developed will help to identify viroid-free rootstock for use in the budwod certification programme.